2000
DOI: 10.1007/s004420051009
|View full text |Cite
|
Sign up to set email alerts
|

Interactive effects of host resistance and drought stress on the performance of a gall-making aphid living on Norway spruce

Abstract: Four full-sib families of Norway spruce (Picea abies), of which two were resistant to a galling aphid (Adelges abietis) and two were susceptible, were exposed to drought stress for 2 years. The primary aim was to test the hypothesis that the various life stages of the aphid differ in their response to environmentally induced changes in the host plant. The drought treatment had a significant negative effect on tree growth. This was reflected in gall size which responded in a similar way to the drought stress, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
40
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(47 citation statements)
references
References 27 publications
6
40
1
Order By: Relevance
“…Several studies have reported the susceptibility of free-feeding insects to the hygrothermal stress to explain the higher incidence on wetlands than in xeric habitats Price, 1988, 1992;Preszler and Price, 1988;Fernandes and Lara, 1993;Price et al, 1998;Blanche, 2000;Björkman, 2000;Blanche and Ludwig, 2001;Lara et al, 2002;Veldtman and Mcgeoch, 2003;Cuevas-Reyes et al, 2004). Our results support this hypothesis as the desiccating factors are more amenable in mesic and interior forest habitats, causing higher herbivory rates by chewing insects on C. quercifolius individuals.…”
Section: Resultssupporting
confidence: 83%
“…Several studies have reported the susceptibility of free-feeding insects to the hygrothermal stress to explain the higher incidence on wetlands than in xeric habitats Price, 1988, 1992;Preszler and Price, 1988;Fernandes and Lara, 1993;Price et al, 1998;Blanche, 2000;Björkman, 2000;Blanche and Ludwig, 2001;Lara et al, 2002;Veldtman and Mcgeoch, 2003;Cuevas-Reyes et al, 2004). Our results support this hypothesis as the desiccating factors are more amenable in mesic and interior forest habitats, causing higher herbivory rates by chewing insects on C. quercifolius individuals.…”
Section: Resultssupporting
confidence: 83%
“…result is opposite to the increase in nitrogen concentration as a consequence of drought supposed by White (1984) when proposing the plant stress hypothesis. Indeed, several studies have reported decreased nitrogen concentration in water-stressed plants (e.g., Inbar et al 2001;Staley et al 2006), while others found no differences in nitrogen concentration between water-stressed and control plants (Björkman 2000;De Bruyn et al 2002). This discrepancy among studies was attributed to nonlinear effects of drought on plant chemistry (Scheirs and De Bruyn 2005;Staley et al 2006).…”
Section: Discussionmentioning
confidence: 91%
“…If a new trait (such as resistance to a specific damaging agent) is to be included in the breeding program, it must be under strong genetic control, be efficiently measurable and clearly contribute to the overall breeding goal. Even though boreal forest trees show great genetic variation in resistance [99][100][101][102][103], the interactive effects of warmer temperatures and other factors, such as day length and food quality, and the potentially improved performance of natural enemies and pathogens, illustrate the possibility of complex outcomes arising in response to climate change [104][105][106]. Many climate scenarios predict that warming will accelerate insect development rate and facilitate range expansions of pests.…”
Section: Adaptations Beyond General Forest Management (In Tree Breedimentioning
confidence: 99%